29.8k views
2 votes
Helppppppppppp!!!!!

Helppppppppppp!!!!!-example-1

2 Answers

5 votes

Answer:

-11

Explanation:

1.) If n=(-3) in
n^(2) +7n+1

2.) Plug in your value for "n".

3.)
(-3)^(2)+ 7(-3) +1

4.) Evaluate

5.)
n^(2) +7n+1 =(-11)

User MamaWalter
by
5.5k points
1 vote

Answer:


n ^(2) + 7n + 1 \\ where \: the \: value \: of \: n = - 3 \\ n ^(2) + 7n + 1 \\ = - 3^(2) + 7( - 3) + 1 \\ = - 9 - 21 + 1 \\ = - 29

User Fancyplants
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.